Teachers' interpretation of the Merdeka curriculum as a policy innovation: A phenomenological exploration - Candra, Gracia Eveline; Wahzudik, Niam (Universitas Negeri Semarang, 2024)
The Merdeka Curriculum significantly changes Indonesia’s education system by granting schools flexibility in designing, implementing, and evaluating learning. This study examines teachers' acceptance of the curriculum, challenges encountered, and strategies for adaptation using a phenomenological qualitative approach. Data were collected through interviews, observations, and document analysis to explore teachers’ interpretations of the curriculum’s innovation attributes: relative advantage, compatibility, complexity, trialability, and observability. Findings indicate that the curriculum enhances learning flexibility and student motivation. Its compatibility with previous practices supports adaptation, though complexity arises from changes in work culture and administrative demands. Trialability is facilitated by mentoring and collaboration, while observability suggests improved student engagement, requiring further evaluation. This study recommends continuous training, resource support, and systematic monitoring to strengthen adoption, with active teacher participation for ongoing feedback.